Teratogenic Potential of Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The effect of antiepileptic drugs on intrauterine growth is reviewed from the Center for Human Molecular Genetics, Nebraska, and the University of Newcastle upon Tyne, UK.